2018
DOI: 10.1111/jen.12514
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the newly identified endoparasitoid Cotesia icipe Fernandez‐Triana & Fiaboe on Spodoptera littoralis (Boisduval)

Abstract: Cotesia icipe Fernandez‐Triana & Fiaboe is a solitary koinobiont larval endoparasitoid, recently discovered in Kenya and new to science, that parasitizes select lepidopteran herbivores of amaranth. We investigated its host range on five commonly encountered amaranth lepidopteran defoliators. Cotesia icipe accepted, successfully and aggressively parasitized the amaranth noctuid defoliators Spodoptera littoralis (Boisduval) and Spodoptera exigua (Hübner), but failed to parasitize Herpetogramma bipunctalis (F.), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…The new associations of native parasitoids with S. frugiperda might be attributable to the occurrence of several other Spodoptera species in West Africa, such as S. exempta, S. exigua and S. littoralis. Interestingly, there is only very little overlap between the parasitoid guild of S. frugiperda and the one associated with cereal stem borers such as Eldana saccharina Walker, Sesamia spp., Busseola fusca (Fuller), and Chilo aleniellus (Strand) [46][47][48][49][50][51].…”
Section: Parasitoid Complex and Parasitism Of S Frugiperda In Ghana mentioning
confidence: 99%
“…The new associations of native parasitoids with S. frugiperda might be attributable to the occurrence of several other Spodoptera species in West Africa, such as S. exempta, S. exigua and S. littoralis. Interestingly, there is only very little overlap between the parasitoid guild of S. frugiperda and the one associated with cereal stem borers such as Eldana saccharina Walker, Sesamia spp., Busseola fusca (Fuller), and Chilo aleniellus (Strand) [46][47][48][49][50][51].…”
Section: Parasitoid Complex and Parasitism Of S Frugiperda In Ghana mentioning
confidence: 99%
“…The parasitism rate obtained for C. icipe on S. exigua when using a single female (9.7%) was lower than that obtained for the same parasitoid on S. littoralis (42.99%; Agbodzavu et al., ). It was also relatively lower compared to the parasitism rates reported for other parasitoids on S. exigua .…”
Section: Discussionmentioning
confidence: 73%
“…Plants infested with second instar larvae of S. littoralis were introduced in ventilated perspex cages as described above in Section 2.2 containing 2‐ to 3‐day‐old mated C. icipe adults. Our preliminary observations showed that second instar larvae were more readily accepted for oviposition by C. icipe and were therefore used (Agbodzavu et al., ). The parasitoids were fed on honey, and hosts were offered to them for oviposition for a period of 24 hr.…”
Section: Methodsmentioning
confidence: 99%
“…52 In this study, we demonstrated that C. icipe had a female-biased ratio in all the host species, a finding similar to previous studies in which C. icipe was found to be female biased irrespective of the host stage attacked on both S. frugiperda 28 and S. littoralis. 25 Other related species that exhibit a female-biased sex ratio irrespective of the host species they were offered include C. plutellae 53 and C. flavipes. 54 The fact that C. icipe is female biased in all the tested hosts, makes it a very promising candidate for biological control of these pests, especially S. frugiperda and S. littoralis.…”
Section: Discussionmentioning
confidence: 99%
“…n. (both Hymenoptera: Trichogrammatidae), 23,24 and larval parasitoids have been reported on fall armyworm across Africa and Asia. 19 Among the larval parasitoids, Cotesia icipe Fernández-Triana & Fiaboe (Hymenoptera: Braconidae), a solitary koinobiont larval parasitoid of Spodoptera littoralis (Boisduval) and Spodoptera exigua (Hübner) (all Lepidoptera: Noctuidae), 25,26 has been found to be a promising parasitoid of S. frugiperda. 24,27,28 However, the cooccurrence and interaction between S. frugiperda and the stemborers (S. calamistis, B. fusca, C. partellus), as well other defoliators such as S. littoralis and Spodoptera exempta (Scott) (Lepidoptera: Noctuidae), which occupy the same agroecological zone or occur on the same host plant, 27,29,30 may have diverse implications for the efficiency of C. icipe as a biocontrol agent of S. frugiperda.…”
Section: Introductionmentioning
confidence: 99%